Degenerately Hydrogen Doped Molybdenum Oxide Nanodisks for Ultrasensitive Plasmonic Biosensing. (18th January 2018) - Zhang, Bao Yue; Zavabeti, Ali; Chrimes, Adam F.; Haque, Farjana; O'Dell, Luke A.; Khan, Hareem; Syed, Nitu; Datta, Robi; Wang, Yichao; Chesman, Anthony S. R.; Daeneke, Torben; Kalantar‐zadeh, Kourosh; et al.
Abstract: Plasmonic biosensors based on noble metals generally suffer from low sensitivities if the perturbation of refractive‐index in the ambient is not significant. By contrast, the features of degenerately doped semiconductors offer new dimensions for plasmonic biosensing, by allowing charge‐based detection. Here, this concept is demonstrated in plasmonic hydrogen doped molybdenum oxides (H x MoO3 ), with the morphology of 2D nanodisks, using a representative enzymatic glucose sensing model. Based on the ultrahigh capacity of the molybdenum oxide nanodisks for accommodating H +, the plasmon resonance wavelengths of H x MoO3 are shifted into visible‐near‐infrared wavelengths. These plasmonic features alter significantly as a function of the intercalated H + concentration. The facile H + deintercalation out of H x MoO3 provides an exceptional sensitivity and fast kinetics to charge perturbations during enzymatic oxidation. The optimum sensing response is found at H1.55 MoO3, achieving a detection limit of 2 × 10 −9 m at 410 nm, even when the biosensing platform is adapted into a light‐emitting diode‐photodetector setup. The performance is superior in comparison to all previously reported plasmonic enzymatic glucose sensors, providing a great opportunity in developing high performance biosensors. Abstract : H x MoO3 plasmonic disks are synthesized. H + and concurrently electrons can be extracted from the host structure during a designed biochemical event. This alteration in charge rapidly changes the plasmon resonance features, hence creating an ultrasensitive platform.